2016
DOI: 10.1002/fuce.201500213
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Water Transport in Polymer Electrolyte Fuel Cells Using Coupled Continuum and Pore‐Network Models

Abstract: Water management remains a critical issue for polymer electrolyte fuel cell performance and durability, especially at lower temperatures and with ultrathin electrodes. To understand and explain experimental observations better, water transport in gas diffusion layers (GDLs) with macroscopically heterogeneous morphologies was simulated using a novel coupling of continuum and pore-network models. X-ray computed tomography was used to extract GDL material parameters for use in the pore-network model. The simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…The pore network determines the morphology as a network of pores and throats where the pores act as reservoirs and the connecting throats define the transport pathways. Several groups have worked with pore network models in defining the transport through porous materials, in applications varying from fuel cell diffusion media,, PEM electrolyzers, redox flow battery electrodes, and rock structures . Banerjee et al .…”
Section: Introductionmentioning
confidence: 99%
“…The pore network determines the morphology as a network of pores and throats where the pores act as reservoirs and the connecting throats define the transport pathways. Several groups have worked with pore network models in defining the transport through porous materials, in applications varying from fuel cell diffusion media,, PEM electrolyzers, redox flow battery electrodes, and rock structures . Banerjee et al .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low computation cost of PNMs, it has recently been integrated into a full MEA model to predict the local saturation and effective properties of the GDL. 50,51 Despite their usefulness, PNMs do not faithfully represent the pore space, so their predictions of water configurations are only rough estimations. This further reduces the reliability of the gas transport predictions as a function of the local saturation in the GDL.…”
Section: 4mentioning
confidence: 99%
“…A pore-network model that has a long history in the study of porous media like soils and rocks 62 has recently been used in understanding water transport in GDL materials. [63][64][65][66][67][68][69] The pore network model maps a complex pore space continuum onto a regular and irregular network of pore bodies and pore throats. Several works have shown that invasion-percolation process, which is a strongly capillary-driven process at the limiting case of zero fluid velocity, may be an important mechanism for water transport in GDL.…”
mentioning
confidence: 99%